Exploring Success Factors for New Product Selling in Fast - Moving Consumer Goods - Kourav, Vivek; Sharma, Arbuda (Indian Journal of Marketing, 2023)
Purpose : Innovations in fast-moving consumer goods (FMCGs) play a substantial role in the growth and sustainability of the FMCG industry. Companies invest resources to design and launch new products to meet evolving consumer demands and to improve their sales effectiveness. Therefore, it is critical to identify the factors that help firms acquire and retain customers for their new products. Several factors have been severally discussed in various contexts and sectors that may affect the success or failure of products. This study tried to consolidate all the factors associated with new product selling in the FMCG sector and identified the hierarchy among these factors. Design : Factors were identified through an exhaustive literature review, and the hierarchical relationships were identified with the help of the total interpretive structural modeling technique. Ajudgmental sample of 19 domain experts was selected for the study. Findings : The findings revealed that labeling and environmental consciousness are the critical respective driving productcentric and consumer-centric factors that influenced other success factors and thus determined the success or failure of new product selling (NPS). Practical Implications : The findings will help the stakeholders in the FMCG industry to develop appropriate strategies for selling new products by taking into account these factors and their hierarchical relationships. Originality/Value : The factors that help firms to succeed in new product selling in the FMCG sector in the Indian context have not been explored in previous research studies. Moreover, this study contributed to developing hierarchical relationships to elucidate the most significant driving factors.